2018
DOI: 10.1016/j.ehj.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding and asymptomatic overdose in patients under Vitamin K antagonist therapy: Frequency and risk factors

Abstract: BackgroundVitamin K antagonists are widely used in the treatment and prevention of thromboembolic disease. However, these drugs can cause serious side effects, especially bleeding. This study aims to evaluate frequency and risk factors of both bleeding and asymptomatic overdose in North African patients undergoing Vitamin K antagonist therapy.MethodsWe performed a cross-sectional study in patients undergoing Vitamin K antagonist therapy. A statistical analysis has been conducted to identify overdose and bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, the safety and efficacy of warfarin are dependent on maintaining the INR value within the target range. This finding was supported in previous studies that had shown that inappropriate INR monitoring increases the risk of bleeding events . Indeed, we observed that supratherapeutic INR values and bleeding events were more frequent in patients treated with an inappropriate dose of warfarin rather with an appropriate dose of warfarin.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the safety and efficacy of warfarin are dependent on maintaining the INR value within the target range. This finding was supported in previous studies that had shown that inappropriate INR monitoring increases the risk of bleeding events . Indeed, we observed that supratherapeutic INR values and bleeding events were more frequent in patients treated with an inappropriate dose of warfarin rather with an appropriate dose of warfarin.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, an inappropriate dose adjustment of warfarin tended to be more frequent in outpatients with a CONUT score !5 than in those with a CONUT score <5 in this study [2/3 (66.7%) vs. 9/22 (40.9%)]. It is known that inappropriate INR monitoring increases the risk of bleeding events [22,23]. We inferred that difficulty in regular monitoring may be one possible reason for an increased risk of MB in malnourished patients receiving warfarin.…”
Section: Main Findingsmentioning
confidence: 54%
“…The global rate of bleeding with the VKA acenocoumarol recorded in this study was comparable to those previously described in some neighbouring and some European countries. [6][7][8] However, this rate was significantly higher than the incidence reported in most Western countries. [9][10][11] This discrepancy in prevalence between countries within a region may be ascribed to differences in socioeconomic status, in management of VKA therapy and differences between experimental and observational studies.…”
Section: Discussionmentioning
confidence: 70%